The Influence of the STAD and NHT Learning Models on Students' Cognitive Achievement and Learning Motivation on Colloid Material in Banyumas - muhammad rasyid nafi (Universitas Pendidikan Ganesha, 2024)
This study aims to assess the impact of the Student Team Achievement Division (STAD) and Numbered Head Together (NHT) learning models on students’ cognitive achievement and learning motivation in colloidal material at MA Negeri 1 Banyumas. The study uses a quantitative approach with a quasi-experimental design, involving students from six XI science classes of MA Negeri 1 Banyumas. The first experimental group was taught using the STAD model, while the second group was taught using the NHT model. The sampling technique used was random sampling. Instruments included multiple-choice tests to measure cognitive achievement and learning motivation. Data analysis was carried out using an independent t-test. The results showed that both the STAD and NHT models had a significant impact on students’ cognitive achievement and learning motivation in colloid material. The p-values ​​for the NHT learning model were 0.47 and 0.39, while the p-values ​​for the STAD learning model were 0.17 and 0.16.